2018
DOI: 10.1007/s11356-018-2659-x
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous silicon alters ascorbate-glutathione cycle in two salt-stressed indica rice cultivars (MTU 1010 and Nonabokra)

Abstract: Silicon is widely available in soil and is known to mitigate both biotic and abiotic stress in plants. Very low doses of silicon are becoming increasingly essential in rice for biofortification and preventing water loss. Soil salinity is a matter of grave concern in various parts of the world, and silicon is a suitable candidate to mitigate salinity-induced stress of important plants in affected areas. The present study investigates the protective capability of exogenously applied silicon in ameliorating NaCl-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(14 citation statements)
references
References 94 publications
1
13
0
Order By: Relevance
“…satabdi than cv. khitish and coincides with the study conducted in rice cultivar MTU 1010 under salinity stress (44). Increase in ascorbate contents under 2 µM selenate occurred due to the antioxidative nature of selenate under mentioned dose.…”
Section: Discussionsupporting
confidence: 87%
“…satabdi than cv. khitish and coincides with the study conducted in rice cultivar MTU 1010 under salinity stress (44). Increase in ascorbate contents under 2 µM selenate occurred due to the antioxidative nature of selenate under mentioned dose.…”
Section: Discussionsupporting
confidence: 87%
“…One more crucial mechanism operative in plants is adaptation to salinity stress by regulating the antioxidant defence system by inducing ascorbate (AsA) and glutathione (GSH), as they play a key role in removing ROS and sustaining cellular redox potential (Das et al, 2018). Our results also reveal that AsA and GSH contents increased against the accumulation of H 2 O 2 to reverse oxidative damage in SS plants.…”
Section: Discussionmentioning
confidence: 56%
“…Moreover, the regulatory pattern is different depending upon plant species and Si intensity. For instance, application of Si enhanced AsA-GSH pathway in two rice cultivars differing in salt tolerance, with the ameliorative effect being more pronounced upon Si administration in the sensitive cultivar [100]. One study on Glycyrrhiza uralensis showed that the exogenous addition of 1, 2, 4, and 6 mM Si could significantly increase POD activity and reduce malondialdehyde (MDA) concentrations compared to salinity stress alone.…”
Section: Mechanisms Of Silicon In Alleviating Salinity Stressmentioning
confidence: 99%